The Power of Precarity and a Generative Gut Check - Mainaly, Shiva (Journal of International Students, 2023)
This cross-border narrative follows an international student’s journey pursuing a Ph.D. in rhetoric and composition at the University of Louisville. Initial challenges I was beset with included communication barriers, adapting to new academic and cultural contexts, and batting self-doubt. Financial strain and COVID-19 amplify concerns about future career prospects. The university’s swift shift to online learning during the pandemic inspires my adaptability. Reflections on the Black Lives Matter (BLM) protests and technology’s limitations challenge prevailing perspectives embraced and enshrined by everyone, including the narrator. The narrative unfolds, prompting reflections on enduring racial inequality despite professed notions of parity. This critical viewpoint extends to examining technology’s limitations, countering much-vaunted hype around techno-optimism. My narrative depicts pandemic-era uncertainties, emphasizing my resolve to confront challenges with courage. It encourages embracing present opportunities to overcome ambiguity and inspire others in similar situations.